PLAYING CARDS AS A MEDIA IN TEACHING WRITTEN DESCRIPTIVE FOR EIGHTH GRADE STUDENTS OF SMP 4 SEMARANG - Yuli Purwanto (Universitas PGRI Semarang, 2013)
This research is aimed: 1) To insvestigate the students ability in written descriptive text taught without playing card in the case of eighth grade students of SMP 4 Semarang in academic year 2013/2014. 2) To insvestigate the students ability in written descriptive text taught by using playing card in the case of eighth grade students of SMP 4 Semarang in academic year 2013/2014. 3) To know the significances between students ability in written descriptive text taught without playing card and taught by using playing card. The final paper used descriptive quantitative method. The sample of this final paper was 8E class of SMP 4 Semarang. The sampling of the final paper was non random sampling. The total sample of the research were 32 students. Instrument of the research were pre-test and post-test. The conclusions from this final paper are: 1) The precentage of the eigth grade students’ ability in written descriptive text taught without playing card were 29% students got A, 41.9% students got B, 12.9% students got C and 16.1% students got D. The mean of the pre test score was 74.45. The students ability in written descriptive text that were taught without using playing card was good. 2) the percentages of the eight grade students ability in written descriptive text who were taught by using playing card were 51.6% students got A, 35.5% students got B, 12.9% students got C. The mean of the post test was 81.32. The student’s ability of writtten descriptive text raised significantly from 74.45 points to 81.32 points (raised 6.87 points). There were no more students who got D or E after they are taught by using playing card. The analysis of pre tes and post test by using SPSS 16 showed that T test was higher than T table (2.528 > 2.222). There was significances of using playing card as media in teaching written descriptive. The students ability in written descriptive text taught by using playing card was very good.